2015
DOI: 10.1074/jbc.m114.592931
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl Oligopeptidase Enhances α-Synuclein Dimerization via Direct Protein-Protein Interaction

Abstract: Background: Prolyl oligopeptidase (PREP) modulates accumulation of aggregated ␣-synuclein both in vitro and in vivo, but the mechanism remains unknown. Results: Using live-cell and cell-free methods, we show that PREP interacts directly with ␣-synuclein. Conclusion: PREP binds to ␣-synuclein and enhances its dimerization. Significance: These results establish a mechanism of how PREP inhibition reduces ␣-synuclein aggregation and support PREP inhibition as a novel therapy in synucleinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(95 citation statements)
references
References 56 publications
6
89
0
Order By: Relevance
“…Our group has done additional experiments on PREP and aSyn interactions, and we have confirmed PREP-aSyn interaction in vitro. Notably, we have shown that PREP increased aSyn dimerization by direct protein-protein interaction [64]. This effect is independent of PREP activity but only treatment of catalytically active PREP with a PREP inhibitor, KYP-2047, reduced aSyn dimerization while the S554A-PREP-mediated aSyn dimerization process remained unchanged.…”
Section: Prep Interacts With Asyn To Increase Its Aggregationmentioning
confidence: 74%
“…Our group has done additional experiments on PREP and aSyn interactions, and we have confirmed PREP-aSyn interaction in vitro. Notably, we have shown that PREP increased aSyn dimerization by direct protein-protein interaction [64]. This effect is independent of PREP activity but only treatment of catalytically active PREP with a PREP inhibitor, KYP-2047, reduced aSyn dimerization while the S554A-PREP-mediated aSyn dimerization process remained unchanged.…”
Section: Prep Interacts With Asyn To Increase Its Aggregationmentioning
confidence: 74%
“…22,38,42 In addition to its involvement in neuroinflammation, PREP has been suggested to play a role in other neurodegenerative diseases and synaptic plasticity. There is evidence that PREP is involved in molecular interactions, eliciting an effect that is independent of its peptidase activity, but nevertheless may be modulated by inhibitor binding.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that PREP is involved in molecular interactions, eliciting an effect that is independent of its peptidase activity, but nevertheless may be modulated by inhibitor binding. 22,38,42 In addition to its involvement in neuroinflammation, PREP has been suggested to play a role in other neurodegenerative diseases and synaptic plasticity. 14,17,23 Furthermore, it has been frequently associated with secretion of neuropeptides and related to cognitive functions in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…PREP is involved in the synthesis of the anti-fibrotic peptide N-acetyl-serylaspartyl-lysyl-proline (97). It has been shown that PREP interacts with α-synuclein and accelerates its aggregation (98,99). Additional interaction partners are glyceraldehyde-3-phosphate dehydrogenase (100), growth-associated protein 43 (101,102) and tubulin (90).…”
Section: Prepmentioning
confidence: 99%